2010
DOI: 10.4132/koreanjpathol.2010.44.5.469
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Endogenous Hypoxic Markers Hypoxia Inducible Factor-1α, Carbonic Anhydrase IX, and Epithelial Mesenchymal Transition Regulator TWIST Expression in Non-small Cell Lung Cancer

Abstract: Background :The epithelial mesenchymal transition (EMT) is intimately associated with tumor hypoxia. The present study was conducted to investigate the immunohistochemical relationship between hypoxic and EMT-related molecules in non-small cell lung carcinoma (NSCLC). Methods : Immunohistochemical staining for hypoxia inducible factor (HIF)-1a, carbonic anhydrase (CA) IX, TWIST, and E-cadherin proteins was performed in 146 cases of NSCLC (80 cases of adenocarcinoma and 66 cases of squamous cell carcinoma) usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…However, the prognostic value of Twist in lung cancer remains controversial. Some studies [ 24 – 26 ] have suggested that the expression of Twist might not predict the survival of NSCLC, while the other researches [ 27 30 ] have indicated a specific correlation between Twist expression and patient prognosis. Besides, the research of Hung et al [ 31 ] suggested Twist was associated with a shorter overall survival (OS), whereas the overexpression of Twist did not influence recurrence-free survival (RFS).…”
Section: Introductionmentioning
confidence: 99%
“…However, the prognostic value of Twist in lung cancer remains controversial. Some studies [ 24 – 26 ] have suggested that the expression of Twist might not predict the survival of NSCLC, while the other researches [ 27 30 ] have indicated a specific correlation between Twist expression and patient prognosis. Besides, the research of Hung et al [ 31 ] suggested Twist was associated with a shorter overall survival (OS), whereas the overexpression of Twist did not influence recurrence-free survival (RFS).…”
Section: Introductionmentioning
confidence: 99%
“…EMT is triggered by a set of stimuli, which include hypoxia and growth factors, and tumor stromal cell interactions with transcription factors such as TWIST, SNAI1, SLUG, and ZWB1 4. TWIST overexpression has also been identified in various kinds of epithelial tumors and plays a distinct role in tumor progression via the loss of E-cadherin expression 6,7,8,9,10,11,12,13,14,15,16…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have identified that reduced E-cadherin expression is associated with more aggressive epithelial tumors. 9 , 12 , 17 , 21 TWIST binds the E-cadherin promoter and inhibits E-cadherin transcription levels, which modulate EMT in cancer progression. An inverse correlation between TWIST upregulation and E-cadherin downregulation was also observed in several types of malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations